1952
DOI: 10.4269/ajtmh.1952.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the “New Guinea B” Strain of Dengue Virus to Suckling and to Adult Swiss Mice

Abstract: Adaptation of the Hawaiian strain of dengue virus to growth in the brain of young adult Swiss mice was a gradual process (1). When serial transfers were made with 10 per cent mouse brain suspensions serving as inocula, it required 15 passages before all of the mice became paralyzed. Once paralysis and death occurred regularly, the titer of the virus could be calculated, and after many further passages it increased from an initial value of about 102 to about 10' LD50 per 0.03 gram of brain tissue. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1956
1956
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The protective efficacy of IgG 5H2 ⌬D was evaluated using a mouse DENV encephalitis model described previously (24,52). Passive transfer of IgG 5H2 ⌬D at a dose of approximately 20 g/mouse afforded 50% protection against challenge with 25 LD 50 of the mouse-neurovirulent DENV-4 strain H241.…”
Section: Discussionmentioning
confidence: 99%
“…The protective efficacy of IgG 5H2 ⌬D was evaluated using a mouse DENV encephalitis model described previously (24,52). Passive transfer of IgG 5H2 ⌬D at a dose of approximately 20 g/mouse afforded 50% protection against challenge with 25 LD 50 of the mouse-neurovirulent DENV-4 strain H241.…”
Section: Discussionmentioning
confidence: 99%
“…Although dengue virus infections in human do not manifest encephalitis symptoms, several other members of the Flavivirus genus cause acute encephalitis in humans, and there is significant homology (35 to 50%) among the E sequences of dengue viruses and other members of the Flavivirus genus. Although DEN4 from an intermediate mouse brain passage level has not been evaluated for utility as a vaccine, dengue virus type 1 and type 2 mutants selected in this manner were shown to be attenuated for humans (16,24,27). Analysis of amino acid changes in these viruses during serial mouse brain passage might help to identify other sequences that confer attenuation for humans and at the same time contribute to mouse neurovirulence.…”
Section: 7mentioning
confidence: 99%
“…Various strategies have been explored to produce an effective vaccine for prevention of dengue virus infection ever since the dengue virus was isolated more than half a century ago. During early studies, serial intracerebral passage of dengue type 1 or type 2 virus in mice was used to attenuate these viruses for development of candidate strains for inclusion in a vaccine to be used in humans (16,(24)(25)(26)(27). Studies by Hotta showed that the Mochizuki strain (dengue type 1) virus lost its virulence for humans after 17 passages in mouse brain (16).…”
mentioning
confidence: 99%
“…Hotta (1952) achieved mouse adaptation of a strain of dengue-1 virus in 6-7 g. mice but did not observe paralysis until after two blind passages. Meiklejohn appears to have been the first to suggest the use of suckling mice for propagation of dengue viruses (Schlesinger & Frankel, 1952). It is because there have been so few successful isolations of dengue viruses and these with difficulty that the isolations reported here are described in detail.…”
Section: Isolation Of the Virusesmentioning
confidence: 99%
“…They failed to adapt strain 'C' directly to adult mice after nine blind passages. Schlesinger & Frankel (1952) adapted the New Guinea 'B' strain of type 2 virus to suckling mice after four passages in DBA mice and two in suckling Swiss mice. Nineteen further passages in sucklings were necessary to adapt the virus to adult mice.…”
Section: Isolation Of the Virusesmentioning
confidence: 99%